2021
DOI: 10.3390/su13020942
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Households’ Sustainable Energy through Gender Attitudes towards Rooftop PV Installations: A Case of the Central Highlands, Vietnam

Abstract: The report shows that there was no disparity between males and females in their attitude to rooftop solar electricity systems (rooftop PV) installations. Government motivation is the key factor that affects householders’ attitudes to rooftop PV. Three other factors—households’ perception, education and environment mentioning—were also crucial for the research model. Meanwhile, six factors had no significant effect on the dependent variables—these consisted of age, gender, rooftop material, level of electricity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
2
3
0
1
Order By: Relevance
“…The energy concern variable shows a significant relationship towards purchase intention; this result is correlating with other studies that are related to SEPs in different geographical areas like India, Vietnam and China (Aggarwal et al , 2019a; Aggarwal et al , 2019b; Jirakiattikul et al , 2021; Zhu et al , 2020). Researchers believe that respondents’ concern towards energy is the first step towards sustainable living and environmental protection.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The energy concern variable shows a significant relationship towards purchase intention; this result is correlating with other studies that are related to SEPs in different geographical areas like India, Vietnam and China (Aggarwal et al , 2019a; Aggarwal et al , 2019b; Jirakiattikul et al , 2021; Zhu et al , 2020). Researchers believe that respondents’ concern towards energy is the first step towards sustainable living and environmental protection.…”
Section: Discussionsupporting
confidence: 85%
“…It has been suggested that customers base their decisions on the information they receive from their social media networks, which they regard as the most dependable source of information (Reyes-Mercado and Rajagopal, 2017); therefore, a sprayand-pray approach will be less effective than creative marketing strategies that target community integration towards SEPs and also by creating positive word-of-mouth for solar technologies through solar champions in their local communities will have a beneficial impact on purchase intent. The energy concern variable shows a significant relationship towards purchase intention; this result is correlating with other studies that are related to SEPs in different geographical areas like India, Vietnam and China (Aggarwal et al, 2019a;Aggarwal et al, 2019b;Jirakiattikul et al, 2021;Zhu et al, 2020). Researchers believe that respondents' concern towards energy is the first step towards sustainable living and environmental protection.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…As a result, this study analysed bivariate correlation to examine the linear relationship and continued to examine the variance inflation factor (VIF) and tolerance to confirm the presence of multicollinearity. The values of tolerance must be less than 5 and tolerance values greater than 0.2 (Jirakiattikul et al, 2021). The multiple linear regression equation is as follow:…”
Section: Resultsmentioning
confidence: 99%
“…Thứ tư, sử dụng điện từ pin năng lượng mặt trời có tác dụng làm giảm khí nhà kính góp phần điều hòa khí hậu. Thân thiện với môi trường, làm giảm tác hại của tia UV lên nhà kính, nguyên lý hoạt động của các thiết bị năng lượng mặt trời không gây bụi, độc hại, tiếng ồn, vô cùng thân thiện với môi trường (Jirakiattikul & Lan, 2021). Để biến tiềm năng năng lượng tái tạo, năng lượng mặt trời của Việt Nam thành hiện thực, bên cạnh các chính sách phù hợp và hiệu quả thì thực hiện chuyển đổi văn hóa môi trường Van Khuc et al, 2021;Q.…”
unclassified